Serum Levels of ifabp2 and Differences in Lactobacillus and Porphyromonas Gingivalis Abundance on Gut Microbiota Are Associated with Poor Therapeutic Response in Rheumatoid Arthritis: A Pilot Study - Tello-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Intestinal dysbiosis is related to the physiopathology and clinical manifestation of rheumatoid arthritis (RA) and the response to pharmacologic treatment. The objectives of this study were (1) to analyze the effect of conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs) on the abundance of gut microbiota’s bacteria; (2) to evaluate the relationship between the differences in microbial abundance with the serum levels of intestinal fatty-acid binding protein 2 (IFABP2), cytokines, and the response phenotype to csDMARDs therapy in RA. A cross-sectional study was conducted on 23 women diagnosed with RA. The abundance of bacteria in gut microbiota was determined with qPCR. The ELISA technique determined serum levels of IFABP2, TNF-α, IL-10, and IL-17A. We found that the accumulated dose of methotrexate or prednisone is negatively associated with the abundance of Lactobacillus but positively associated with the abundance of Bacteroides fragilis. The Lactobacillus/Porphyromonas gingivalis ratio was associated with the Disease Activity Score-28 for RA with Erythrocyte Sedimentation Rate (DAS28-ESR) (r = 0.778, p = 0.030) and with the levels of IL-17A (r = 0.785, p = 0.027) in the group treated with csDMARD. Moreover, a relation between the serum levels of IFABP2 and TNF-α (r = 0.593, p = 0.035) was observed in the group treated with csDMARD. The serum levels of IFABP2 were higher in patients with secondary non-response to csDMARDs therapy. In conclusion, our results suggest that the ratios of gut microbiota’s bacteria and intestinal permeability seems to establish the preamble for therapeutic secondary non-response in RA. © 2023 by the authors.